Regular at‐home abdominal paracentesis via Tenckhoff catheter in patients with refractory congestive heart failure. Issue 12 (5th October 2021) - Kunin, Margarita; Mini, Sharon; Abu‐Amer, Nabil; Beckerman, Pazit
Abstract: Background: Peritoneal dialysis (PD) is increasingly used for the long‐term management of refractory congestive heart failure (CHF). Patients with severe CHF and ascites were treated with regular at‐home abdominal paracentesis via Tenckhoff catheter. We investigated the outcome of those patients, aiming to identify potential prognostic factors for longer survival. Methods: Patients with refractory CHF referred by cardiologists to the PD unit from years 2009 to 2019 and treated with regular at‐home abdominal paracentesis via Tenckhoff catheter without peritoneal exchanges, were enrolled into this prospective observational study. Results: From the total of 69 refractory CHF patients treated with PD, 18 (26%) were managed with regular at‐home abdominal paracentesis via Tenckhoff catheter and improved without the need for peritoneal exchanges for fluid removal (no peripheral oedema or pulmonary congestion) or for solutes removal. Median survival of severe CHF patients treated with abdominal paracentesis was 13.5 months (0‐34 months). Long‐term survivors demonstrated significant improvement in the New York Heart Association (NYHA) functional class, improvement in kidney function and decrease in serum C‐reactive protein (CRP) and Brain natriuretic peptide (BNP) compared with their baseline status. A subgroup of patients with shorter survival were more likely to have evidence of liver cirrhosis and significantly lower serum sodium compared with patients with longer survival. Conclusions: Refractory CHF patients with massive ascites could be successfully treated with regular at‐home abdominal paracentesis via Tenckhoff catheter. This treatment provides a useful alternative to periodical percutaneous paracentesis on as‐needed basis.